Protein crystallography - James, Michael (Henry Stewart Talks, 2007)
Protein crystallography, Protein crystallization methods, Crystal symmetry, X-ray intensity data collection, Electron density equation, The Patterson function, Multiple isomorphous replacement phasing, Fitting the electron density with a model, Refinement of the model, Estimating quality of the model
Archived at 2016/06/22